Sulfur-doped carbon-based composite wave-absorbing material as well as preparation method and application thereof

By introducing sulfur doping and magnetic substances into the carbon-based material, the problems of poor impedance matching and narrow absorption frequency band of carbon-based materials are solved, and efficient and multiple electromagnetic wave absorption effects are achieved.

CN119677074APending Publication Date: 2025-03-21DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202311578947.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-09-21
Filing Date
2023-11-23
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

Carbon-based materials have problems such as poor impedance matching, narrow absorption frequency band, large filling thickness and single attenuation mechanism in terms of electromagnetic wave absorption.

Method used

By using sulfur-containing sulfonated resin, sulfur doping is introduced after heat treatment, defects and functional groups are formed as dipole centers, dipole polarization is induced under high-frequency electromagnetic fields, and electromagnetic energy is converted into thermal energy through relaxation loss. At the same time, magnetic substances are introduced and evenly distributed through ion exchange, increasing magnetic loss and effective absorption bandwidth.

Benefits of technology

The dielectric loss capability of the material is improved, the multiple electromagnetic loss mechanism is realized, and the effective absorption frequency band is expanded. The material is light in weight, thin in thickness and strong wave absorption performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119677074A_ABST
    Figure CN119677074A_ABST
Patent Text Reader

Abstract

The invention discloses a sulfur-doped carbon-based composite wave-absorbing material as well as a preparation method and application thereof. Sulfonated resin is used as a carbon source, is impregnated with a salt solution of iron, nickel, cobalt and other metals, and then is subjected to high-temperature carbonization in an inert atmosphere, so that the sulfur-doped carbon-based composite wave-absorbing material is prepared. The content of the magnetic components in the composite wave-absorbing material can be adjusted by adjusting the concentration of the metal salt solution, and the electromagnetic wave absorption performance can be further adjusted and controlled in a wide range. The raw material components are stable, the cost is low, and the preparation method is simple and suitable for industrial production; sulfur-containing sulfonated resin is used, after heat treatment, a defect and a functional group introduced by sulfur doping serve as a dipole center, dipole polarization is induced under a high-frequency electromagnetic field, and the dielectric loss capacity of the material can be improved; the composite wave-absorbing material has multiple electromagnetic loss mechanisms, and is wide in effective absorption frequency band, light in weight, thin in thickness and high in wave-absorbing performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a sulfur-doped carbon-based composite absorbing material and a preparation method and application thereof, belonging to the field of absorbing materials. Background Art

[0002] With the rapid development of electronic communication technology, the problem of electromagnetic interference is becoming increasingly severe. Electromagnetic wave absorbing materials can convert electromagnetic energy into heat energy to achieve electromagnetic wave attenuation, becoming an effective means to solve the problem of electromagnetic wave pollution. Therefore, researchers from all over the world focus on the development and utilization of absorbing materials. Traditional absorbing materials can no longer meet the requirements of development. New electromagnetic wave absorbing materials must have the characteristics of thin thickness, light weight, high absorption intensity and wide absorption bandwidth. Carbon-based materials have become one of the most promising electromagnetic wave absorbing materials due to their low density, high stability and excellent thermal and electrical conductivity. However, carbon-based materials have problems such as poor impedance matching and a single attenuation mechanism. Therefore, the performance of carbon-based absorbing materials can be optimized through strategies such as structural regulation, doping modification and construction of composite materials. The research and development of high-performance and low-filling carbon-based absorbing materials has great practical significance in the field of electromagnetic wave protection. Summary of the invention

[0003] In order to solve the problems of poor impedance matching, narrow absorption band, large filling thickness and single attenuation mechanism of carbon-based materials, the present application uses a sulfur-containing sulfonated resin. After heat treatment, the defects and functional groups introduced by sulfur doping act as dipole centers, induce dipole polarization under high-frequency electromagnetic fields, and convert electromagnetic energy into heat energy through relaxation losses. Various heterogeneous interfaces including solid-air interfaces and sulfur atoms and carbon matrix interfaces can also produce interface polarization to attenuate electromagnetic waves. In addition, the introduction of sulfur functional groups locally changes the hybridization of carbon atoms and enhances surface polarity, which also brings about interface polarization and related relaxation. The conductivity increases the imaginary part of the complex dielectric constant, promotes the transmission of free electrons under the action of electromagnetic fields, thereby increasing the dielectric loss of the material and consuming microwave energy. At the same time, magnetic substances are introduced into the material, and the magnetic substances can be evenly distributed in the carbon layer by ion exchange. On the basis of the original dielectric loss, magnetic loss is increased, the effective absorption bandwidth is increased, and the absorption performance of electromagnetic waves can be regulated in different frequency bands.

[0004] This application adopts the following technical solutions:

[0005] A sulfur-doped carbon-based composite absorbing material, comprising resin-derived carbon doped with sulfur atoms and a magnetic component supported on the surface of the resin-derived carbon;

[0006] The resin-derived carbon doped with sulfur atoms is obtained by carbonizing at least one sulfonated resin selected from polystyrene resin, phenolic resin and epoxy resin;

[0007] In the sulfur-doped carbon-based composite absorbing material, the doping amount of sulfur atoms is 1-25wt%.

[0008] Optionally, the magnetic component is selected from at least one of Fe3O4, Co3O4, NiO, Fe7S8, Co9S8, and Ni9S8;

[0009] Optionally, in the sulfur-doped carbon-based composite absorbing material, the content of the magnetic component is 0.01 to 60 wt %.

[0010] According to another aspect of the present application, a method for preparing the above-mentioned sulfur-doped carbon-based composite absorbing material is also provided, comprising the following steps:

[0011] The sulfonated resin is immersed in a solution containing a metal salt, stirred, dried, and carbonized to obtain the sulfur-doped carbon-based composite wave-absorbing material.

[0012] The preparation method of the present application is simple, the effective absorption frequency band is wide, the wave absorbing performance is strong, the weight is light, and the thickness is thin.

[0013] Optionally, the sulfur content in the sulfonated resin is 1 to 30 wt%.

[0014] Optionally, the sulfur content in the sulfonated resin is selected from any value of 1wt%, 2wt%, 3wt%, 4wt%, 5wt%, 10wt%, 15wt%, 20wt%, 25wt%, 30wt%, or any range therebetween.

[0015] Optionally, the solid-liquid ratio of the sulfonated resin to the solution containing the metal salt is 1:1-5.

[0016] Optionally, the metal salt is selected from at least one of ferric sulfate, ferric nitrate, ferric chloride, ferric acetate, nickel sulfate, nickel nitrate, nickel chloride, nickel acetate, cobalt sulfate, cobalt nitrate, cobalt chloride and cobalt acetate;

[0017] Optionally, in the solution containing the metal salt, the content of the metal salt is 1 to 50 wt %;

[0018] Optionally, in the solution containing the metal salt, the solvent is selected from at least one of water, ethanol and acetone.

[0019] Optionally, the stirring time is 2 to 24 hours;

[0020] Optionally, the drying temperature is 80-150°C.

[0021] Optionally, the carbonization conditions include: a temperature of 500 to 900° C., a heating rate of 1 to 5° C. / min, a carbonization time of 1 to 8 hours, and the carbonization is performed under an inactive atmosphere.

[0022] Optionally, the inert atmosphere is selected from at least one of nitrogen, helium and argon.

[0023] According to another aspect of the present application, there is also provided the above-mentioned sulfur-doped carbon-based composite absorbing material, and at least one of the sulfur-doped carbon-based composite absorbing materials prepared by any of the above-mentioned preparation methods is used as an electromagnetic wave absorber in military and civilian electromagnetic compatibility and protection.

[0024] Optionally, the application includes: mixing the sulfur-doped carbon-based composite absorbing material with a binder and then coating and curing the mixture.

[0025] Optionally, the binder is selected from at least one of paraffin, epoxy resin, unsaturated polyester resin, phenolic resin and silicone resin.

[0026] The beneficial effects of this application include:

[0027] The sulfur-doped carbon-based composite absorbing material provided by the present application has stable raw material composition, low cost, simple preparation method, and is suitable for industrial production; using sulfur-containing sulfonated resin, after heat treatment, the defects and functional groups introduced by sulfur doping act as dipole centers, inducing dipole polarization under high-frequency electromagnetic fields, and can improve the dielectric loss capacity of the material; this composite absorbing material has multiple electromagnetic loss mechanisms, a wide effective absorption bandwidth, light weight, thin thickness, and strong absorbing performance.

[0028] The preparation method of the sulfur-doped carbon-based composite absorbing material provided in the present application uses a sulfur-containing sulfonated resin. After heat treatment, the defects and functional groups introduced by sulfur doping act as dipole centers, induce dipole polarization under high-frequency electromagnetic fields, and convert electromagnetic energy into heat energy through relaxation losses. Various heterogeneous interfaces including solid-air interfaces and sulfur atoms and carbon matrix interfaces can also produce interface polarization to attenuate electromagnetic waves. In addition, the introduction of sulfur functional groups locally changes the hybridization of carbon atoms and enhances surface polarity, which also brings about interface polarization and related relaxation. The conductivity increases the imaginary part of the complex dielectric constant, promotes the transmission of free electrons under the action of electromagnetic fields, thereby increasing the dielectric loss of the material and consuming microwave energy. At the same time, the sulfonated resin is used as a carbon source, and the salt solution of metals such as iron, nickel, and cobalt is impregnated and carbonized at high temperature under an inert atmosphere to obtain a sulfur-doped carbon-based composite absorbing material. The content of magnetic components such as Fe3O4, Co3O4, NiO, Fe7S8, Co9S8, Ni9S8 in the composite absorbing material can be adjusted by adjusting the concentration of the metal salt solution, thereby further realizing the regulation of the electromagnetic wave absorption performance in a wider range. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1This is a TEM image of the sulfur-doped carbon-based composite absorbing material obtained in Example 1, with a scale of 50 nm.

[0030] Figure 2 This is a reflection loss diagram of the sulfur-doped carbon-based composite absorbing material obtained in Example 2.

[0031] Figure 3 This is a physical picture of the composite absorbing material prepared from the sulfur-doped carbon-based composite absorbing material obtained in Example 2 and epoxy resin.

[0032] Figure 4 This is a reflection loss diagram of the sulfur-doped carbon-based composite absorbing material obtained in Comparative Example 1. DETAILED DESCRIPTION

[0033] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.

[0034] Unless otherwise specified, the raw materials in the examples of this application were purchased through commercial channels.

[0035] Example 1

[0036] Step 1: Impregnation: Dissolve ferric nitrate in deionized water to prepare a metal salt solution. Impregnate 10g of sulfonated resin in 20g of 1wt% metal salt solution, stir for 4h, filter and dry in a drying oven at 120℃;

[0037] Step 2: Put the resin obtained after drying in step 1 into an atmosphere furnace, heat it from room temperature to 750°C at 5°C / min under a nitrogen atmosphere, carbonize it at a constant temperature for 2 hours, and cool it naturally to room temperature to obtain a sulfur-doped carbon-based composite absorbing material.

[0038] Figure 1 This is a TEM image of the resin-derived carbon composite absorbing material obtained in Example 1, with a scale of 50 nm.

[0039] Embodiment 2:

[0040] Step 1: Impregnation: Dissolve ferric nitrate in deionized water to prepare a metal salt solution. Impregnate 10g of sulfonated resin in 20g of 25wt% metal salt solution, stir for 4h, filter and dry in a drying oven at 120℃;

[0041] Step 2: Put the resin obtained after drying in step 1 into an atmosphere furnace, heat it from room temperature to 750°C at 5°C / min under a nitrogen atmosphere, carbonize it at a constant temperature for 2 hours, and cool it naturally to room temperature to obtain a sulfur-doped carbon-based composite absorbing material.

[0042] Figure 2This is a reflection loss diagram of the sulfur-doped carbon-based composite absorbing material calculated according to the electromagnetic parameters in Example 2. It can be seen from the figure that the reflection loss peak value of the material is -78.96dB. When the thickness is 2.65mm, the reflection loss value is less than -10dB, that is, the effective absorption bandwidth is 6.98GHz.

[0043] Figure 3 The composite absorbing material is prepared by uniformly mixing the sulfur-doped carbon-based composite absorbing material obtained in Example 2 with an epoxy resin and an epoxy resin curing agent in a mass ratio of 1:4:1.

[0044] Embodiment 3:

[0045] Step 1: Impregnation: Dissolve ferric nitrate in deionized water to prepare a metal salt solution. Impregnate 10g of sulfonated resin in 20g of 50wt% metal salt solution, stir for 4h, filter and dry in a drying oven at 120℃;

[0046] Step 2: Put the resin obtained after drying in step 1 into an atmosphere furnace, heat it from room temperature to 750°C at 5°C / min under a nitrogen atmosphere, carbonize it at a constant temperature for 2 hours, and cool it naturally to room temperature to obtain a sulfur-doped carbon-based composite absorbing material.

[0047] Embodiment 4:

[0048] Step 1: Impregnation: Dissolve ferric nitrate in deionized water to prepare a metal salt solution. Impregnate 10g of sulfonated resin in 20g of 25wt% metal salt solution, stir for 4h, filter and dry in a drying oven at 120℃;

[0049] Step 2: Put the resin obtained after drying in step 1 into an atmosphere furnace, heat it from room temperature to 500°C at 5°C / min under a nitrogen atmosphere, carbonize it at a constant temperature for 2 hours, and cool it naturally to room temperature to obtain a sulfur-doped carbon-based composite absorbing material.

[0050] Embodiment 5:

[0051] Step 1: Impregnation: Dissolve ferric nitrate in deionized water to prepare a metal salt solution. Impregnate 10g of sulfonated resin in 20g of 25wt% metal salt solution, stir for 4h, filter and dry in a drying oven at 120℃;

[0052] Step 2: Put the resin obtained after drying in step 1 into an atmosphere furnace, heat it from room temperature to 900°C at 5°C / min under a nitrogen atmosphere, carbonize it at a constant temperature for 2 hours, and cool it naturally to room temperature to obtain a sulfur-doped carbon-based composite absorbing material.

[0053] Embodiment 6:

[0054] Step 1: Impregnation: Dissolve ferric acetate in deionized water to prepare a metal salt solution. Impregnate 10g of sulfonated resin in 20g of 25wt% metal salt solution, stir for 4h, filter and dry in a drying oven at 120℃;

[0055] Step 2: Put the resin obtained after drying in step 1 into an atmosphere furnace, heat it from room temperature to 750°C at 5°C / min under a nitrogen atmosphere, carbonize it at a constant temperature for 2 hours, and cool it naturally to room temperature to obtain a sulfur-doped carbon-based composite absorbing material.

[0056] Embodiment 7:

[0057] Step 1: Impregnation: Dissolve ferric sulfate in deionized water to prepare a metal salt solution. Impregnate 10g of sulfonated resin in 20g of 25wt% metal salt solution, stir for 4h, filter and dry in a drying oven at 120℃;

[0058] Step 2: Put the resin obtained after drying in step 1 into an atmosphere furnace, heat it from room temperature to 750°C at 5°C / min under a nitrogen atmosphere, carbonize it at a constant temperature for 2 hours, and cool it naturally to room temperature to obtain a sulfur-doped carbon-based composite absorbing material.

[0059] Embodiment 8:

[0060] Step 1: Impregnation: Dissolve cobalt nitrate in deionized water to prepare a metal salt solution. Impregnate 10g of sulfonated resin in 20g of 25wt% metal salt solution, stir for 4h, filter and dry in a drying oven at 120℃;

[0061] Step 2: Put the resin obtained after drying in step 1 into an atmosphere furnace, heat it from room temperature to 750°C at 5°C / min under a nitrogen atmosphere, carbonize it at a constant temperature for 2 hours, and cool it naturally to room temperature to obtain a sulfur-doped carbon-based composite absorbing material.

[0062] Embodiment 9:

[0063] Step 1: Impregnation: Dissolve ferric nitrate and cobalt nitrate in deionized water at a ratio of 1:1 to prepare a metal salt solution. Impregnate 10g of sulfonated resin in 20g of 25wt% metal salt solution, stir for 4h, filter and dry in a drying oven at 120℃;

[0064] Step 2: Put the resin obtained after drying in step 1 into an atmosphere furnace, heat it from room temperature to 750°C at 5°C / min under a nitrogen atmosphere, carbonize it at a constant temperature for 2 hours, and cool it naturally to room temperature to obtain a sulfur-doped carbon-based composite absorbing material.

[0065] Comparative Example 1:

[0066] Step 1: Impregnation: Dissolve ferric nitrate in deionized water to prepare a metal salt solution. Impregnate 10g of sulfonated resin in 20g of 60wt% metal salt solution, stir for 4h, filter and dry in a drying oven at 120℃;

[0067] Step 2: Put the resin obtained after drying in step 1 into an atmosphere furnace, heat it from room temperature to 750°C at 5°C / min under a nitrogen atmosphere, carbonize it at a constant temperature for 2 hours, and cool it naturally to room temperature to obtain a sulfur-doped carbon-based composite absorbing material.

[0068] Figure 4 This is the reflection loss diagram of the sulfur-doped carbon-based composite absorbing material calculated according to the electromagnetic parameters of Comparative Example 1. It can be seen from the figure that the reflection loss peak value of the material is -13.52dB. When the thickness is 8.86mm, the reflection loss value is less than -10dB, that is, the effective absorption bandwidth is 1.48GHz.

[0069] Comparative Example 2:

[0070] Step 1: Impregnation: Dissolve ferric nitrate in deionized water to prepare a metal salt solution. Impregnate 10g of sulfonated resin in 20g of 25wt% metal salt solution, stir for 4h, filter and dry in a drying oven at 120℃;

[0071] Step 2: Put the resin obtained after drying in step 1 into an atmosphere furnace, heat it from room temperature to 1000°C at 5°C / min under a nitrogen atmosphere, carbonize it at a constant temperature for 2 hours, and cool it naturally to room temperature to obtain a sulfur-doped carbon-based composite absorbing material.

[0072] The test results of the minimum reflection loss, effective absorption bandwidth, and matching thickness of Examples 1 to 9 and Comparative Examples 1 to 2 are shown in Table 1:

[0073] Table 1

[0074]

[0075]

[0076] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.

Claims

1. A sulfur-doped carbon-based composite absorbing material, characterized in that: The sulfur-doped carbon-based composite absorbing material comprises resin-derived carbon doped with sulfur atoms and a magnetic component supported on the surface of the resin-derived carbon; The resin-derived carbon doped with sulfur atoms is obtained by carbonizing at least one sulfonated resin selected from polystyrene resin, phenolic resin and epoxy resin; In the sulfur-doped carbon-based composite absorbing material, the doping amount of sulfur atoms is 1-25wt%.

2. The sulfur-doped carbon-based composite absorbing material according to claim 2, characterized in that: The magnetic component is selected from at least one of Fe3O4, Co3O4, NiO, Fe7S8, Co9S8, and Ni9S8; Preferably, in the sulfur-doped carbon-based composite absorbing material, the content of the magnetic component is 0.01-60wt%.

3. The method for preparing the sulfur-doped carbon-based composite absorbing material according to claim 1 or 2, characterized in that: The following steps are involved: The sulfonated resin is immersed in a solution containing a metal salt, stirred, dried, and carbonized to obtain the sulfur-doped carbon-based composite wave-absorbing material.

4. The preparation method according to claim 3, characterized in that: The sulfur content in the sulfonated resin is 1 to 30 wt%; Preferably, the solid-liquid ratio of the sulfonated resin to the solution containing the metal salt is 1:1-5.

5. The preparation method according to claim 3, characterized in that: The metal salt is selected from at least one of ferric sulfate, ferric nitrate, ferric chloride, ferric acetate, nickel sulfate, nickel nitrate, nickel chloride, nickel acetate, cobalt sulfate, cobalt nitrate, cobalt chloride, and cobalt acetate; Preferably, in the solution containing the metal salt, the content of the metal salt is 1 to 50 wt %; Preferably, in the solution containing the metal salt, the solvent is selected from at least one of water, ethanol and acetone.

6. The preparation method according to claim 3, characterized in that: The stirring time is 2 to 24 hours; Preferably, the drying temperature is 80-150°C.

7. The preparation method according to claim 3, characterized in that: The carbonization conditions include: a temperature of 500 to 900° C., a heating rate of 1 to 5° C. / min, a carbonization time of 1 to 8 hours, and the carbonization is performed under an inactive atmosphere.

8. Application of at least one of the sulfur-doped carbon-based composite absorbing material according to claim 1 or 2 and the sulfur-doped carbon-based composite absorbing material prepared by the preparation method according to any one of claims 3 to 7 as an electromagnetic wave absorber in military and civilian electromagnetic compatibility and protection.

9. The use according to claim 8, characterized in that: The application comprises: mixing the sulfur-doped carbon-based composite absorbing material with a binder and then coating and curing the mixture.

10. The use according to claim 9, characterized in that: The binder is selected from at least one of paraffin, epoxy resin, unsaturated polyester resin, phenolic resin and silicone resin.

Citation Information

Cited By

  • Multi-element doped binary composite carbon material as well as preparation method and application thereof

    CN120504313A

  • A multi-element doped binary composite carbon material and its preparation method and application

    CN120504313B